VD_FINDINFO Pron / 2014 / 55 vom 29. Oktober 2014 - VD Tribunal cantonal (2014)
AVOCAT, MODÉRATION, HONORAIRES CALCULÉS EN FONCTION DU RÉSULTAT POSITIF, DÉPENS | 45 al. 1 LPAv, 50 al. 1 LPAv, 50 al. 3 LPAv, 50 al. 4 LPAv, 48 LPA-VD, 55 LPA-VD